PROSES PELIPUTAN BERITA âLINTAS PAGIâ RRI SEMARANG DALAM PERSPEKTIF KOMUNIKASI ISLAMI - Ardani, Ahdini Rizqi (Islamic Communication Journal, 2018)
Radio is an auditive communication media with several characteristics, among them is a crosshairs and contain interference. Listening to radio programs can only be done once. One of the radio programs is news. Dissemination of information and news via radio can take place quickly and wider. Broadcast news on the radio must be true, once the news is wrong in broadcast it is not possible to repeat again. Because the listener may only hear the error, do not hear what is rectified. It may also be that the listener did not hear the error, so that the wrong message rectified is correct. In the context of Islamic communication spreading good, true, and honest news is a must. Islamic communication is a way of communicating that is Islamic, which is not contrary to the teachings of the Quran and Hadith.This study aims to describe the news coverage process "Lintas Pagi" RRI Semarang in the perspective of islamic communication. This research is a descriptive qualitative research by using data analysis technique Miles and Huberman.Based on research conducted on the news coverage of "Lintas Pagi" RRI Semarang, then obtained the result that the news coverage process "Lintas Pagi" RRI Semarang in the perspective of Islamic communication without realizing has applied the principles of Islamic communication. These principles are qawlan sadidan, qawlan baligha, qawlan karima, qawlan marufan, qawlan layyina, and qawlan maisura.Keywords: news coverage , morning news, islamic communication perspective-----------------------------------------------------------------------------------Radio merupakan media komunikasi auditif dengan beberapa karakteristik, di antaranya adalah selintas dan mengandung gangguan. Mendengarkan program radio hanya dapat dilakukan sekali. Salah satu program radio adalah berita. Penyebaran informasi dan berita melalui radio dapat berlangsung cepat dan lebih luas. Menyiarkan berita di radio harus benar, sekali berita tersebut salah dalam menyiarkan tidak mungkin di ulang kembali. Karena pendengar mungkin hanya mendengar ralatnya saja, tidak mendengar apa yang diralat. Mungkin pula pendengar tidak mendengar ralatnya, sehingga berita salah yang diralat dianggapnya benar.Â  Dalam konteks komunikasi islami menyebarkan berita yang baik, benar, dan jujur adalah sebuah keharusan. Komunikasi islami merupakan cara berkomunikasi yang bersifat islami, yang tidak bertentangan dengan ajaran Al-Qurâan dan Hadits.Penelitian ini bertujuan untuk mendeskripsikan proses peliputan berita âLintas Pagiâ RRI Semarang dalam perspektif komunikasi islami. Penelitian ini merupakan jenis penelitian deskriptif kualitatif dengan menggunakan teknik analisis data Miles dan Huberman,Berdasarkan penelitian yang dilakukan terhadap proses peliputan berita âLintas Pagiâ RRI Semarang, maka diperoleh hasil bahwa proses peliputan berita âLintas Pagiâ RRI Semarang dalam perspektif komunikasi islami tanpa di sadari telah menerapkan prinsip-prinsip komunikasi islami. Prinsip-prinsip ini yaitu qawlan sadidan, qawlan baligha, qawlan karima, qawlan maârufan, qawlan layyina, dan qawlan maisura.Â Kata kunciÂ Â Â Â Â  :Â  liputan berita, Â lintas pagi, perspektif komunikasi islami